WANPRESTASI PT. SENTOSA BUMI WIJAYA DALAM PERJANJIAN JUAL BELI TANDAN BUAH SEGAR (TBS) KELAPA SAWIT DENGAN KOPERASI UNIT DESA KEMBANG SARI DI KABUPATEN BENGKAYANG - NIM. A1011211108, LAILA LITATA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Distributing or trading books without the permission of the copyright holder is an illegal activity and violates the Copyright Law No. 28 of 2014 and the ITE Law. Therefore, for those who violate the law, the law will provide clear sanctions. The problem of this writing is whether the copyright holder for the sale of novel books sold on E-Commerce without permission has received legal protection according to copyright law. The purpose of this study is to find out and analyze how the application of copyright law as a form of copyright protection in the sale of pirated books that occur on E-Commerce platforms and to find out and analyze the legal consequences for parties involved in the sale of pirated books through E-Commerce platforms in accordance with the provisions of the Copyright Law No. 28 of 2014. In this study, a legislative approach was applied that refers to the Copyright Law No. 28 of 2014 and Law No. 11 of 2008 which has been amended to Law No. 19 of 2016 concerning Information and Electronic Transactions (ITE Law) as the main reference to gain an understanding of the legal protection of copyright holders. The research method used is normative research, which is carried out by examining literature materials or secondary data. It then gathers the necessary information that leads to the identification of the problem and finally the resolution of the problem. This research is supported by various primary and secondary data sources in the form of literature research on the legal protection of copyright holders, including the Copyright Law No. 28 of 2014 and various references to journals and related books. The results of this study show that the importance of implementing the Copyright Law to protect copyright holders is due to the increasing prevalence of pirated novel books on various e-commerce platforms. Selling pirated books without a license can cause legal consequences according to Law Number 28 of 2014 concerning Copyright, it can be in the form of civil and criminal law, such as fines, imprisonment, or civil lawsuits. The benefits of this research are to provide an understanding of the application of the Copyright Law as a form of protection, with the strengthening of the law, cooperation between the government, online platforms, and the public, effective public awareness, can reduce the sale of pirated books and protect the copyrights of legitimate authors and publishers. Keywords: Legal Protection, Copyright, Piracy, E-Commerce Abstrak Mengedarkan atau memperjualbelikan buku tanpa izin pemegang hak cipta merupakan kegiatan ilegal dan melanggar Undang-Undang Hak Cipta No. 28 Tahun 2014 dan UU ITE. Maka dari itu, bagi mereka yang melanggar hukum, undang-undang akan memberikan sanksi yang jelas. Permasalahan dari penulisan ini adalah apakah pemegang hak cipta atas penjualan buku novel yang dijual di E-Commerce tanpa ijin telah mendapatkan perlindungan hukum sesuai undang-undang hak cipta. Tujuan penelitian ini adalah untuk mengetahui dan menganalisis bagaimana penerapan undang-undang hak cipta sebagai bentuk perlindungan hak cipta dalam penjualan buku bajakan yang terjadi di platform E-Commerce serta untuk mengetahui dan menganalisis mengenai akibat hukum terhadap pihak-pihak yang terlibat dalam penjualan buku bajakan melalui platform E-Commerce sesuai dengan ketentuan Undang-Undang Hak Cipta No. 28 Tahun 2014.Dalam penelitian ini, menerapkan pendekatan perundang-undangan yang mengacu pada Undang-Undang Hak Cipta No. 28 Tahun 2014 dan Undang-Undang No. 11 Tahun 2008 yang telah diubah menjadi Undang-Undang No. 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik (UU ITE) sebagai rujukan utama untuk memperoleh pemahaman tentang perlindungan hukum pemegang hak cipta. Metode penelitian yang digunakan adalah penelitian bersifat normatif, yang dilakukan dengan cara meneliti bahan pustaka atau data sekunder. Kemudian mengumpulkan informasi yang diperlukan yang mengarah pada identifikasi masalah dan akhirnya penyelesaian masalah. Penelitian ini didukung oleh berbagai sumber data primer dan sekunder berupa penelitian kepustakaan mengenai perlindungan hukum pemegang hak cipta, antara lain UU Hak Cipta No. 28 Tahun 2014 dan berbagai reverensi jurnal dan buku terkait. Hasil penelitian ini menunjukkan bahwa pentingnya penerapan Undang-Undang Hak Cipta untuk melindungi pemegang hak cipta yang dikarenakan semakin marak terjadinya penjualan buku novel bajakan diberbagai platform e-commerce. Menjual buku bajakan tanpa izin dapat menimbulkan akibat hukum sesuai Undang Nomor 28 Tahun 2014 Tentang Hak Cipta, dapat berupa hukum perdata dan pidana, seperti denda, penjara, maupun gugatan perdata. Manfaat penelitian ini guna memberikan pemahaman atas penerapan UU Hak Cipta sebagai bentuk perlindungan,dengan penguatan hukum, kerja sama antara pemerintah, platform online, dan masyarakat, kesadaran publik yang efektif, dapat mengurangi penjualan buku bajakan dan melindungi hak cipta para penulis dan penerbit sah. Kata Kunci : Perlindungan Hukum, Hak Cipta, Pembajakan, E-Commerce